2020
DOI: 10.1002/aenm.202000945
|View full text |Cite
|
Sign up to set email alerts
|

The Fast Charge Transfer Kinetics of the Lithium Metal Anode on the Garnet‐Type Solid Electrolyte Li6.25Al0.25La3Zr2O12

Abstract: The charge transfer kinetics between a lithium metal electrode and an inorganic solid electrolyte is of key interest to assess the rate capability of future lithium metal solid state batteries. In an in situ microelectrode study run in a scanning electron microscope, it is demonstrated that—contrary to the prevailing opinion—the intrinsic charge transfer resistance of the Li|Li6.25Al0.25La3Zr2O12 (LLZO) interface is in the order of 10−1 Ω cm2 and thus negligibly small. The corresponding high exchange current d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 75 publications
3
145
1
Order By: Relevance
“…In a recent study by Krauskopf et al, a novel operando setup was investigated, comprising a flat lithium counter electrode attached to a polished Al‐doped Li 7 La 3 Zr 2 O 12 (LLZO) SE and an in situ‐formed Li metal microelectrode grown onto a tungsten needle. [ 90 ] By achieving a very clean (and stable) interface between the atomically smooth LLZO surface and the freshly formed Li metal, they could show that the charge‐transfer resistance at such interface is negligibly small and therefore not a performance‐limiting factor for the lithium anode in SSB cells, as had been believed previously. This enables very fast lithium‐plating rates, far beyond practical requirements.…”
Section: Characterization Techniquesmentioning
confidence: 82%
See 1 more Smart Citation
“…In a recent study by Krauskopf et al, a novel operando setup was investigated, comprising a flat lithium counter electrode attached to a polished Al‐doped Li 7 La 3 Zr 2 O 12 (LLZO) SE and an in situ‐formed Li metal microelectrode grown onto a tungsten needle. [ 90 ] By achieving a very clean (and stable) interface between the atomically smooth LLZO surface and the freshly formed Li metal, they could show that the charge‐transfer resistance at such interface is negligibly small and therefore not a performance‐limiting factor for the lithium anode in SSB cells, as had been believed previously. This enables very fast lithium‐plating rates, far beyond practical requirements.…”
Section: Characterization Techniquesmentioning
confidence: 82%
“…In contrast to TEM, operando scanning electron microscopy (SEM) has so far only been used to study phenomena related to the Li metal anode of inorganic SE‐based SSBs. [ 88–90 ] Because of the lower spatial resolution offered by SEM, such studies typically focus on macroscopic (chemo)mechanical processes. In a seminal work, Nagao et al followed the lithium plating/stripping at different current densities between a stainless steel current collector and the SE 20P 2 S 5 ‐80Li 2 S using Li metal as counter electrode.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…When attaching lithium to a polished interface by hand, an interfacial resistance of >1 kΩ cm 2 is obtained. It was shown that this high value is in fact not intrinsic to the material combination, but can rather be explained by current constriction, which originates from surface inhomogeneities [23,24] . These can either be impurity phases, like Li 2 CO 3 , or morphological roughness due to polishing with SiC‐paper.…”
Section: Resultsmentioning
confidence: 99%
“…were already able to show via microelectrode studies that the charge transfer between a garnet ISE (LLZO) and the LMA is inherently fast and not rate‐limiting [23] . Interfacial resistances measured in macroscopic cells can rather be interpreted as constriction resistances, as full contact between the LMA and ISE is prevented by pores and surface contaminations [20,23,24] . It was furthermore observed that insufficient vacancy diffusion in lithium itself limits its performance under anodic currents.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Although the production of sintered bulk samples produced by solid-state reaction with a high electrolyte thickness of several hundred micrometers allows remarkable current densities of up to 6 mA cm À2 at 60 C with high solid electrolyte conductivities of up to 10 À3 S cm À1 at room temperature, a commercial industrial large-scale production with high throughput rates in combination with moisture-free processing is challenging. [9][10][11] Ideally, the thickness of the electrolyte should be in the range of 5-20 μm to reduce the risk of short circuits on the one hand but, on the other hand, provide a low electrolyte mass for high cell energy densities. [12] Although much research has been conducted, the thickness range for LLZO films significantly below 50 μm could only rarely been realized yet due to the nonavailability of suitable ceramic production technologies.…”
mentioning
confidence: 99%